2008
DOI: 10.1038/nrm2407
|View full text |Cite
|
Sign up to set email alerts
|

The septin family of GTPases: architecture and dynamics

Abstract: Septins comprise a conserved family of proteins that are found primarily in fungi and animals. These GTP-binding proteins have several roles during cell division, cytoskeletal organization and membrane-remodelling events. One factor that is crucial for their functions is the ordered assembly of individual septins into oligomeric core complexes that, in turn, form higher-order structures such as filaments, rings and gauzes. The molecular details of these interactions and the mechanism by which septin-complex as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
282
1
31

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(317 citation statements)
references
References 115 publications
3
282
1
31
Order By: Relevance
“…The annulus structure was completely absent in all spermatozoa analyzed. c Western blot analysis for septin 4 which was not detected in the gel; PC positive control Septin proteins belong to the GTPase superclass of P loop NTPases [10][11][12]. Sept4 null mice show the reproductive phenotypes similar to a subset of asthenozoospermic patients [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The annulus structure was completely absent in all spermatozoa analyzed. c Western blot analysis for septin 4 which was not detected in the gel; PC positive control Septin proteins belong to the GTPase superclass of P loop NTPases [10][11][12]. Sept4 null mice show the reproductive phenotypes similar to a subset of asthenozoospermic patients [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of the SEPT2-SEPT6-SEPT7 complex was recently solved and revealed that septins form non-polar filaments unlike actin and microtubules [Sirajuddin et al, 2007]. Despite the significance of these structural insights [Barral and Kinoshita, 2008;Weirich et al, 2008], it remains to be determined how septins function as a distinct component of the cytoskeleton.…”
Section: Septins: a Novel Component Of The Cytoskeletonmentioning
confidence: 99%
“…8). Mammalian septins are evolutionary conserved proteins that form filaments associated with cytoskeleton organization, membrane dynamics, mitosis, cytokinesis, and cell cycle progression (9,10). Recently, accumulating data suggest that some septin family members also participate in the pathogenesis of neoplasia (11) and neurodegenerative diseases (12).…”
Section: Introductionmentioning
confidence: 99%